Chapter 28 Media effects on perceptions of societal problems Belief formation in fragmented media environments - Shehata, Adam (Taylor & Francis, 2021)
This chapter focuses specifically on how the news media influence perceptions of societal problems. This research question is discussed and reviewed in three ways. First, to better understand the context and contingencies of media effects on societal perceptions specifically, the outcome variable is related to the broader literature on sociotropic beliefs and cognitive schema theory. Second, classic theories of media effects focusing on societal perceptions are reviewed. The relevance and viability of these theories are discussed in light of the dramatic media environmental transformations of the last two decades. Third, a model of conditional media effects on sociotropic beliefs in contemporary high-choice media environments is proposed and discussed. The chapter concludes with some suggestions for future research on media effects on sociotropic beliefs.